The Immediate Post-Operative Radiograph is an Unreliable Measure of Coronal Plane Alignment in Total Knee Replacement - Petterwood, Joshua; Dowsey, Michelle M.; Rodda, Daevyd; Choong, Peter F. M. (Frontiers in Surgery, 2014)
Background - Restoration of a neutral mechanical axis is a primary goal of total knee replacement (TKR). A mechanical axis within three degrees of neutral has been correlated with improved implant longevity, function and patient satisfaction. We hypothesise that the immediate post-operative radiograph is an unreliable method of measuring alignment following TKR surgery. Methods - 75 consecutive patients had supine x-rays performed on day two post-operatively followed by standing LLR six weeks post-operatively. Correlation was sought between the mechanical axis measured on the LLR and surrogate markers of alignment on the post-operative x-ray including component alignment and an estimation of anatomical alignment using the available length of femoral and tibial shafts. Inter and intra-observer reliability were assessed. Results - The mean mechanical axis was 180.5 (SD 3.0, range 175.1-187.1). Mean offset between anatomical axis and mechanical axis was 6.4 degrees. Inter- and intra-observer agreement were high on all measures. Using the Bland-Altman method demonstrated high levels of disagreement between measurements from short and LLR that included clinically important discrepancies of up to 7 degrees in multiple cases. Conclusion - The long leg weight bearing x-ray is an essential tool to accurately assess coronal plane alignment post TKR. Whilst the immediate post-operative x-ray taken supine provides useful information to the surgeon on any immediate complications our results indicate that it cannot be relied upon to determine correct restoration of the mechanical axis.